Mechanical Properties of Weathered Feldspar Sandstone after Experiencing Dry-Wet Cycles - Wen-bo An; Laigui Wang; He Chen (Advances in Materials Science and Engineering)
Weathering is one of the important geological hazards to many stone cultural relics carved on feldspar sandstone (such as the Datong Yungang Grottoes). To study the mechanical properties of the weathered Yungang Grottoes, feldspar sandstone was subjected to comparative dry-wet cycle tests with water-rock interaction (Group A) and salt-rock interaction (Group B). The variation patterns of the macroscopic physical and mechanical parameters as well as the micro/mesoscopic structures of the two groups of feldspar sandstone with the number of dry-wet cycles were measured. The results showed that for the Group A and Group B sandstones, as the number of dry-wet cycles increased the saturated water absorption and the longitudinal wave velocity increased, with the maximum variation rates reaching 28.02%, 36.98%, 16.20%, and 33.27%. The peak strength and elastic modulus gradually decreased, with the maximum variation rate reaching 48.53%, 73.44%, 26.61%, and 72.39%. The surface height deviation increased by as much as 1.06 μm and 3.34 μm. The mechanism of weathering for the water-rock interaction included three effects, namely, the hydrolysis of the K-Na feldspar, the water swelling of the clay minerals such as kaolinite, and the dissolution of the soluble minerals. The mechanism of weathering for the salt-rock interaction included salt crystallization in the pores or fissures and chemical reactions between the minerals (such as feldspar and calcite) and sulfate, in addition to the above three effects. Therefore, the crystallization stress of the salt exerted the most notable effect on the deterioration of the feldspar sandstone. The results are expected to provide a reference for the stability evaluation and protection of the rock mass of the Grottoes.